1996
DOI: 10.1097/00004728-199607000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Volume Maps with Dynamic Contrast-Enhanced T1-Weighted FLASH Imaging: Normal Values and Preliminary Clinical Results

Abstract: The proposed method is easy to apply in clinical routine MR investigations and provides valuable information for noninvasive, preoperative assessment of tumor grading. It can also provide additional criteria for estimating the histological outcome and with it the degree of ischemia in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The area under the curve describing the temporal change of the relaxation rate DR 1 = (DT 1 ) À1 or DR 2 * = (DT 2 *) À1 during bolus passsage has been demonstrated to be proportional to the CBV (Belliveau et al, 1990;Hacklander et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The area under the curve describing the temporal change of the relaxation rate DR 1 = (DT 1 ) À1 or DR 2 * = (DT 2 *) À1 during bolus passsage has been demonstrated to be proportional to the CBV (Belliveau et al, 1990;Hacklander et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic methods, including the Dynamic Susceptibility Contrast method (Moonen et al, 1992;Rosen et al, 1991;Villringer et al, 1988) and the T 1 bolus method (Dean et al, 1992;Hacklander et al, 1996Hacklander et al, , 1997, are based on the intravascular indicator dilution theory (Meier and Zierler, 1954) and require high temporal resolution to acquire series of images during the first pass of the bolus of the injected tracer in the brain tissue. The area under the curve describing the temporal change of the relaxation rate DR 1 = (DT 1 ) À1 or DR 2 * = (DT 2 *) À1 during bolus passsage has been demonstrated to be proportional to the CBV (Belliveau et al, 1990;Hacklander et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However susceptibility based techniques have significant disadvantages related to spatial distortion occurring in areas of paramagnetic variation and residual relaxivity effects in areas of extravascular contrast leakage. This has led several workers to try to derive CBV maps from T 1 weighted data (25)(26)(27)(28)(29). Although these methods showed some promise they are not routinely used, largely because of their tendency to give rise to erroneously high estimates of CBV in areas of extravascular contrast leakage.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a small number of studies have shown that CBV can be measured with DCE-MRI in normal brain tissue and infarction (24)(25)(26) and may be more accurate than DSC-MRI (27). The feasibility of measuring CBF, which requires a higher temporal resolution, has been demonstrated more recently (28,29).…”
mentioning
confidence: 99%
“…The feasibility of measuring CBF, which requires a higher temporal resolution, has been demonstrated more recently (28,29). In tumors, where blood volumes are typically higher, CBV measurement is inherently less problematic (26), has equal diagnostic quality as DSC-MRI (30), and can be performed simultaneously with a measurement of permeability (31)(32)(33).…”
mentioning
confidence: 99%